Uranium tailings in the Istiqlol city: history, problems, solutions - N. U. Khakimova; M. A. Zoitova (Радиационная гигиена)
The article provides an overview of the problems associated with the uranium tailings in Istiqlol city. Many uranium heritage sites in Central Asia, including the uranium tailings in Istiqlol, hadn’t been mothballed before the collapse of the USSR. The burial complex consists of a quarry, dumps of the “Poor Ores Factory”, an unpreserved open mine, destroyed industrial buildings and four tailings which contain 12 million tons of the uranium production waste. In the area of the tailings, the ambient dose rate of gamma radiation is 0.5–0.6 μSv/h, and at some points it reaches 3.0–4.0 μSv/h. The average annual radon emission from the surface is estimated at 3.9×1011 Bq/year. The contaminated areas also include the Sarym-Sakhly Sai stream, mine, industrial and quarry waters, which are characterized by an increased content of 234U, 238U and 226Ra. The facilities aren’t physically fenced, allowing free access for the public and livestock. Natural disasters such as mudflows, landslides, and earthquakes can lead to an ecological disaster. Attention is paid to the ways of solving problems such as monitoring radionuclides in water, soil, and air; working with the local population to inform and involve them in rehabilitation work; donors search. The Program for the Implementation of the National Concept for the Rehabilitation of Tailings of Uranium Ore Processing Wastes for 2016–2024 was developed and approved by the Government of the Republic of Tajikistan to minimize the radiation impact on the population and the environment. Implementation of the Program requires significant financial investments and trained personals in the field of radiation safety. Only through the joint efforts of the state, population and international organizations is it possible to fully carry out rehabilitation works. Only by joint the state, public, and international organizations efforts, it is possible to solve these problems. Also, one of the main reasons why the population had received unnecessary overexposure was its ignorance of the danger of using water, soil and building materials contaminated with radionuclides. Therefore, the culture of radiation safety should be studied starting from middle school, where students will be taught about ionizing radiation and possible ways of exposure. Then, both cases of intake of radionuclides into the body, which could have been avoided, and radiophobia among the population living near the extraction and processing of uranium ore, will be much lower. Some social and economic aspects are also touched upon.